Effects of COVID-19 on non-communicable diseases and their surveillance in 10 African Union member countries - Adelard Kakunze; Fabian Moser; Betty K. Ingabire; Dumsani N. Mamba; Giselle Sarganas; Eva P. Renggli; Michael Zobi; Angela Fehr; Mohammed Abdulaziz (Journal of Public Health in Africa)
Background: During health emergencies, continuity of care for non-communicable diseases (NCDs) and mental health (MH), informed by robust surveillance, is required. The COVID-19 pandemic revealed that many countries were ill-prepared in this respect.